Dialogo, tolleranza e libertà religiosa in Nigeria (Stato, Chiese e pluralismo confessionale, 2011)
Il contributo, segnalato dal Prof. Raffaele Coppola e dal Prof. Nicola Colaianni, è destinato alla pubblicazione negli Atti del Convegno sul tema “Rilevanza dei diritti cultural-religiosi dei cittadini immigrati nell’ordinamento italiano ed europeo” (Bari, 11 dicembre 2009) tenuto presso l’Università degli Studi “Aldo Moro”.SOMMARIO: 1. Considerazioni introduttive – 2. Luci ed ombre in materia di tolleranza e libertà religiosa – 3. La religione in Nigeria come strumento di integrazione nazionale – 4. Attuazione e inattuazione della libertà religiosa nel contesto sociale – 5. La reintroduzione della Shari’a: un problema aperto – 6. Le “sfide” democratiche.Abstract: With this essay the Author analyses the characteristics of religious freedom in Nigerian legal system, which is considered part of a wider legal phenomenon, what is called the African legal system. Considering the issues related to the religious attitude of the African peoples, and in particular that of the Nigerian ones, the Author underlines the influence exercised by the various religious creeds on other spheres of public life. Besides, in this context one has to take into account the fact that both traditional cultures and political framework have been deeply influenced by the British colonial power. Finally, in this essay the Author also analyses some aspects concerning the fundamental rights in Nigeria, including the religious rights: the way these rights have been recognised and implemented in Nigerian legal system.